GAS HYDRATES EXTRACTION - Abdullah, N.; Pedchenko, M.; Pedchenko, N. (Academic journal. Industrial Machine, Building Civil Engineering, 2017)
The work is dedicated to alternative energy sources, namely extraction of methane gas from gas hydrate fields. In Ukraine they are represented by gas hydrate fields of the Black Sea. The technology of methane extraction from the sea gas hydrates is suggested. Three basic methods of gas extraction from the gas hydrate-bearing reservoirs are known, namely: pressure reduction lower than the pressure equilibrium of hydrates formation at the designed temperature; heating gas hydrate-containing rock to the temperature exceeding the temperature balance; gas hydrate bearing formations disintegration. All the above methods require high energy consumption. It is suggested to enrich sea gas hydrate-bearing formations directly in the field they underlay in. The purpose of the present study is developing and analyzing the gas hydrates extraction method, which is characterized by the absence of the phase transitions at gas hydrates extraction from the productive stratum and, consequently, by the increased versatility and the economical efficiency of the process. Separate steps of the enrichment process are set for this purpose. The suggested technology requires extracting the main bulk of gas hydrates without energy consumption for the phase transition. Meanwhile, it is suggested to dissociate part of gas hydrate in the rock on account of the sea water’s low potential energy. Keywords: gas hydrates, gas hydrates reservoir, dissociation, enrichment. Абдуллах